2004
DOI: 10.1159/000077500
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chromosomal imbalance to sperm selection and pre-implantation loss in translocation-heterozygous Chinese hamsters

Abstract: Chinese hamster stocks with various structurally abnormal chromosomes have been produced by X irradiation. Among these stocks, 18 with various reciprocal translocations were used to investigate the participation of unbalanced gametes in fertilization and the development of unbalanced embryos. Among males as well as females heterozygous for the same translocation, there is no difference in the frequency of each disjunctional class. The participation of chromosomally unbalanced gametes in fertilization was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, it remains possible that aneuploidy for other chromosomes and other types of chromosomal abnormalities may affect sperm maturation and fertilizing capacity. Indeed, results obtained with translocation carriers in Chinese hamsters suggested that sperm carrying specific chromosomal imbalances failed to participate in fertilization (Sonta et al, 1991; Sonta, 2004).…”
Section: Methods For Investigating Paternally‐transmitted Chromosomalmentioning
confidence: 99%
“…However, it remains possible that aneuploidy for other chromosomes and other types of chromosomal abnormalities may affect sperm maturation and fertilizing capacity. Indeed, results obtained with translocation carriers in Chinese hamsters suggested that sperm carrying specific chromosomal imbalances failed to participate in fertilization (Sonta et al, 1991; Sonta, 2004).…”
Section: Methods For Investigating Paternally‐transmitted Chromosomalmentioning
confidence: 99%
“…Chromosomal abnormalities may lead not only to meiotic disturbances and gameto genic disruption, but also to the production of chromo somally unbalanced gametes. Normally, gametes with chromosomal abnormalities have reduced reproductive potential, since the natural selection reduces the proba bility of fertilization, embryonic cell division and implantation of embryos with some types of chromo somal abnormalities [8][9][10]. ART utilization, espe cially intracytoplasmic sperm injection, bypasses this natural barrier to fertilization, increasing the risk of 1 The article was translated by the authors.…”
Section: Introductionmentioning
confidence: 99%